Been there, done that : how our history shows what we can overcome - Jackson, Greg (Simon & Schuster, 2026)
It may be 250 years since this country's founding, but the playbook has remained mostly the same. From the Founding Father's hyperpartisan print war of the 1790s, to the caning of Senator Charles Sumner in 1856, to the thoroughly corrupt presidential election of 1876, and all the way through the yellow journalism and print war of Joseph Pulitzer and William Randoph Hearst, you will recognize how familiar these stories are to our own supposedly unprecedented times.